Security safeguards on e-Payment systems in Malaysia: an analysis on the Payment Systems Act 2003 - Zulhuda, Sonny; Abdul Ghani Azmi, Ida Madieha (International Association of IT Lawyers (IAITL), 2011)
Central to the infrastructure of electronic commerce activities is the electronic payment system. This encompasses not only the issues of technical sophistication but also legal readiness. In the context of electronic commerce environment in Malaysia, this paper seeks to highlight and examine the Malaysian legal readiness in the aspect of electronic payment system, focusing on its Payment Systems Act 2003. The discussion is limited to the issue of electronic security measures embodied in the law. Within its restricted scope, this paper seeks to demonstrate how the law recognizes the importance of security measures in order to build confidence and trust among the public and mainly the users of electronic payments in the country. (Keywords: Security, electronic payment, electronic commerce, Payment Systems Act 2003).